Determinants of Foreign Students' Success at the Czech Universities - Do, Viet Anh; Koblovský, Petr; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This study analyzes determinants of students' success using various of perspectives (sociological, psychological, economic, cultural, organizational) in order to find out related influences. Our theoretical framework predominantly base on personal insights and experience as the author himself was able to spend a lot of time with immigrant students. This research was delimitated to baccalaureate students. The reason is that the linguistic, institutional, cultural and other effects are more distinct and might change enrollment conditions and requirements ex tunc. Our study data collection was empirically analyzed and result into varied findings. Basically, both studied immigrant students groups (Vietnamese and post-Soviet) are academically considerably weaker. This should be caused by their study limited barriers, which were theoretically assumed by an author. Therefore, this study is conceptualized to explore specific limitations.
Vedoucí práce: Petr Koblovský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses